Handbook on anti-money laundering and combating the financing of terrorism for nonbank financial institutions. (Metro Manila, Philippines Asian Development Bank, 2017)
The handbook provides guidance to nonbank financial institutions (NBFIs) on how to manage risks related to money laundering and the financing of terrorism and is intended to assist NBFIs in developing and implementing policies and procedures to combat money laundering and the financing of terrorism. The information contained in the handbook should be adapted to reflect the nature of activities, products, and services offered by individual NBFIs as there is no one size fits all approach to the management of risk.
Keywords: Money laundering -- Prevention; Money laundering investigation; Terrorism -- Finance -- Prevention; Terrorism -- Prevention..; Electronic books